Mutation analysis of a 10-gene panel for colorectal cancer in Huizhou, Guangdong Province of China - Jun Li (SAGE Publishing, 2021)
Objective This study aimed to investigate the type and frequency of mutations in 10 genes in 85 colorectal cancer (CRC) patients in Huizhou and the guiding significance of targeted drug use. Methods The 10-gene panel next-generation sequencing (NGS) was used to assess genetic variants in 85 CRC patients from the Huizhou area combined with clinical information for a comprehensive analysis. Results Upon initial mutation testing, 68% (58/85) were positive. The mutation frequencies of these genes, including KRAS, PIK3CA, NRAS, ERBB2, BRAF, EGFR, and PDGFRA , were 51%, 20%, 5%, 4%, 4%, 1%, and 1%, respectively. Overall, 29 mutation types were detected from seven genes. More mutations were detected in more advanced cancers. There were three samples with multiple mutations of a single gene, including KRAS (n = 2) and ERBB2 (n = 2), 12 samples with multiple mutations of double genes, including KRAS/PIK3CA (n = 10), BRAF/PIK3CA (n = 1), and NRAS/PIK3CA (n = 1), and one sample with multiple mutations of three genes, including ERBB2/KRAS/PIK3CA (n = 1). Theoretically, 27 patients could receive targeted treatment. During the actual treatment, 10 patients received bevacizumab, cetuximab, or fruquintinib with no progression ranging from 12 to 24 months. Conclusion Gene mutations detected by a 10-gene panel were useful for targeting therapy of CRC in Huizhou.